Emergenza e marginalità: la nostra barbàrie. Responsabilità edcucative - Maria Vittoria Isidori (Firenze University Press, 2012)
The theme of marginality - understood as an existential condition of substantial alienation and exclusion of people from the social, cultural, political and productive processess of so-called organized societies - is becoming more prominent in the contemporary pedagogical debate. Particular attention should be paid to the risk of disseminating a widespread culture of marginality in emergency and post-emergency situations, by their very nature subject to phenomena of brutal acculturization and massive deculturization.